2003
DOI: 10.1021/jp030026n
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition and Adsorption Orientation of 2-Fluoroethanol on Clean and Oxidized Cu(100)

Abstract: Temperature-programmed reaction/desorption and reflection−absorption infrared spectroscopy have been employed to investigate the thermal reactions and adsorption geometry of FCH2CH2OH molecules on clean and oxygen-preadsorbed Cu(100) surfaces. Molecular desorption predominates in heating FCH2CH2OH adsorbed on clean Cu(100). However, ∼20% adsorbed FCH2CH2OH molecules at about half-monolayer coverage dissociate on the surface to form water, ethylene, and 1,4-dioxane. On the other hand, monolayer FCH2CH2OH comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The nature of carbon-halogen bonds and metal surfaces are anticipated to affect the reaction routes of XCH 2 CH 2 OH on metal surfaces. On Cu(1 0 0), our recent studies have shown that FCH 2 CH 2 OH and ClCH 2 CH 2 OH are mainly adsorbed reversibly, in contrast to the case of BrCH 2 CH 2 OH [7][8][9]. On oxygen-precovered Cu(1 0 0), ICH 2 CH 2 OH and BrCH 2 CH 2 OH have been reported to dissociate to form -CH 2 CH 2 O-at 115 K [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of carbon-halogen bonds and metal surfaces are anticipated to affect the reaction routes of XCH 2 CH 2 OH on metal surfaces. On Cu(1 0 0), our recent studies have shown that FCH 2 CH 2 OH and ClCH 2 CH 2 OH are mainly adsorbed reversibly, in contrast to the case of BrCH 2 CH 2 OH [7][8][9]. On oxygen-precovered Cu(1 0 0), ICH 2 CH 2 OH and BrCH 2 CH 2 OH have been reported to dissociate to form -CH 2 CH 2 O-at 115 K [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Reflection-absorption infrared spectra taken after exposing 1.5 L HSCH 2 CH 2 OH to Cu(1 0 0) at 115 K and flashing the surface to the indicated temperatures. All the spectra were recorded at 115 K. tions of C-O and CH 2 stretching vibrations of HSCH 2 CH 2 OH in liquid state, suggesting that the moiety of SCH 2 CH 2 OH remains intact after HSCH 2 CH 2 OH adsorption on Cu(1 0 0) at 115 K. In the RAIRS study of 2.0 L FCH 2 CH 2 OH on oxygen-precovered Cu(1 0 0), the C-O stretching frequency is red-shifted from 1095 cm À1 to 1072 cm À1 as FCH 2 CH 2 OH is transformed into FCH 2 CH 2 O-between 160 and 220 K [8]. On the contrary, the C-O stretching vibrations of HO-CH 2 CH 2 -generated from HOCH 2 CH 2 I decomposition on Ag(1 1 1) and Ag(1 1 0) absorb at 1070 and 1076 cm À1 , respectively, which are close to the 1073 cm À1 of ICH 2 CH 2 OH in matrix and to the 1068 cm À1 of ICH 2 CH 2 OH in liquid state [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…2 shows the coverage-dependent temperature-programmed reaction/desorption spectra representing desorption of CH 4 , C 2 H 4 , and CH 3 CHO at HSCH 2 CH 2 OH exposures 61.5 L. HSCH 2 CH 2 OH predominantly decomposes on Cu(1 0 0) to evolve C 2 H 4 between 300 and 400 K. It is known that dissociation of O-H bonds of alcohol molecules is accelerated on oxygen-precovered Ag and Cu surfaces with respect to the clean surfaces. For example, FCH 2 CH 2 OH dissociates by O-H bond scission on oxygen-precovered Cu(1 0 0) between 160 and 220 K [8]. It is likely that deprotonation of OH of HSCH 2 CH 2 OH also occurs at such low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…C 2 H 5 OH [5,6] and FCH 2 CH 2 OH [7] have been reported to form the corresponding ethoxides on O/Cu(1 0 0) by O-H bond dissociation. Alkyl iodides decompose on Cu(1 1 1), via C-I bond scission, to form adsorbed alkyl groups [8].…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 1(a) is due to O-H bond scission of XCH 2 CH 2 OH; (b) and (c) are due to C-X bond scission followed by the formation of C-Cu bond and C-O bond respectively; (d) and (e) are generated from concomitant breakage of C-X and O-H bonds. Note that surface intermediates of XCH 2 CH 2 -and -CH 2 CH 2 -are not considered, because the reaction pathway of C-O bond breakage of alcohol molecules on Cu or O/Cu surface has never been observed [5][6][7]. In the present study, we have found that ICH 2 CH 2 OH decomposes into an oxametallacycle (-CH 2 CH 2 O-) on O/Cu surface at 115 K, but ClCH 2 CH 2 OH dissociates into chloroethoxy (ClCH 2 CH 2 O-) between 170 and 210 K. -CH 2 CH 2 O-reacts on O/Cu(1 0 0) to form ethylene and acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%